A novel space vector modulation strategy for legs parallel three-level inverters to reduce common-mode voltage. Issue 1 (1st November 2022) - He, Haiyang; Zhang, Guorong; Chen, Weilun; Wu, Zhizhen
Abstract : In order to increase the converter's rated power, the parallel connection of legs between inverters has been an effective way. The common-mode voltage is one of the main problems of this inverter. Based on the special connection mode of legs parallel inverter, the output voltage can be regarded as the output of a five-level inverter. Therefore, this paper proposes a space vector modulation based on the virtual five-level to suppress common-mode voltage. The traditional SVPWM algorithm contains a lot of trigonometric function calculation, which slows down the response speed of the system. This paper proposes a novel coordinate system division method, which avoids trigonometric function calculation and reduces the amount of calculation. The effectiveness of this method is verified by Matlab / Simulink simulation.